Desain dan Implementasi Modul Pembelajaran Akhlak Berbasis Humanis-Religius untuk Mengatasi Perilaku Body Shaming di MAS Al-Washliyah Pasar V Medan - Rayni azhari harahap; Nurman Ginting (At Turots: Jurnal Pendidikan Islam, 2026)
This study aims to design and implement a humanist-religious moral learning module as an effort to overcome body shaming behavior among students at MAS Al-Washliyah Pasar V Medan. This study uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. Data collection was carried out through observation, questionnaires, and expert validation, then analyzed descriptively qualitatively and quantitatively. The results of the descriptive statistical analysis show that the module obtained an average score of 3.50 in the appearance aspect, 3.69 in content/material, 3.37 in language, 3.83 in humanist-religious value, and 3.57 in module benefits, which are in the good to very good category. The implementation of the module shows an increase in students' understanding and awareness of the negative impacts of body shaming as well as the growth of empathy and mutual respect. Thus, the humanist-religious moral learning module is suitable for use in Islamic Religious Education learning.